THE EFFECT OF DIGITAL COMPETENCE AND KNOWLEDGE MANAGEMENT ON HEALTH WORKER PERFORMANCE THROUGH WORK INNOVATION AT MAKASSAR CITY REGIONAL GENERAL HOSPITAL - Hendra Gunawan (Universitas Ichsan Sidenreng Rappang, 2023)
This study aims to analyze the effect of digital competence and knowledge management on health worker performance through work innovation at Makassar City Regional General Hospital. This research employed a quantitative approach with individual health workers as the unit of analysis. Data were collected from 98 health workers and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results show that digital competence has a positive and significant effect on work innovation, knowledge management has a positive and significant effect on work innovation, digital competence has a positive and significant effect on health worker performance, knowledge management has a positive and significant effect on health worker performance, and work innovation has a positive and significant effect on health worker performance. The indirect effect testing also indicates that work innovation mediates the effects of digital competence and knowledge management on health worker performance. The R-square value shows that work innovation is explained by digital competence and knowledge management by 0.505, while health worker performance is explained by digital competence, knowledge management, and work innovation by 0.602. These findings confirm that strengthening digital capability and knowledge governance should be directed toward innovative behavior to improve health worker performance measurably.